COMPARISON DEGREE OF ADJECTIVES - Ni Luh Desy Suari Dewi (LPPM Universitas Dhyana Pura, 2016)
ABSTRACT There are many topics and materials of English which can be taught at school to university. One of the most interesting materials is about comparison. Comparison is the process for comparingthing, person or places through the level of quantity, quality or relation. In comparison degree, there are some rules that must be followed in changing the adjectives form. The discussions ofthis study are focused on the definition and the form of degree of comparison, and also the students’ understanding in the form of degree of comparison. The data in this study were takenfrom twelve students of eighth grade students by giving them two worksheets about comparisondegree. The technique which is used in analyzing the data is qualitative. The data will be analyzed based on theory of comparison degree especially about the form of comparative andsuperlative degree to know the students’ understanding about comparison degree. Based on the discussion, it can be concluded that the eighth grade students had known about the comparison,but they must be more aware in changing the basic form of adjectives into the comparative andsuperlative form. Therefore, the students need to study more about the rule of changing the basic form of adjective into the comparative and superlative form. Key words: Adjective, comparison degree, comparative degree, superlative degree ABSTRAK Terdapat berbagai macam topik dan materi bahasa Inggris yang bisa dipelajari di sekolahsampai tingkat universitas. Salah satu materi yang paling menarik adalah tentang perbandingan. Perbandingan adalah sebuah proses membandingkan sesuatu, orang ataupuntempat dalam hal kualitas, kuantitas ataupun tingkat hubungan. Dalam perbandingan, ada beberapa aturan yang harus diperhatikan dalam mengubah bentuk kata sifat sesuai dengantingkat perbandingannya. Pembahasan dalam tulisna ini menitikberatkan pada definisi dan bentuk – bentuk perbandingan serta pemahaman siswa terhadap bentuk – bentuk yang adadalam perbandingan. Data dalam tulisan ini diambil dari 12 orang siswa SMP yang duduk dikelas delapan. Teknik yang digunakan dalam analisa data adalah teknik kualitatif. Data yang diperoleh akan dianalisa berdasarkan teori tingkat perbandingan terutama tentang perubahanbentuk dasar kata sifat menjadi bentuk komparatif dan superlatif untuk mengetahui kemampuan siswa dalam tingkat perbandingan. Berdasarkan hasil analisa, dapat disimpulkan bahwa siswakelas delapan telah mengetahui tentang materi perbandingan, akan tetapi siswa harus lebihberhati-hati dalam mengubah kata sifat dalam tingkat perbandingan komparatif dan superlatif. Oleh sebab itu, siswa harus lebih banyak mempelajari aturan-aturan dalam mengubah kata sifatdalam perbandingan. Kata kunci: Kata sifat, perbandingan, perbandingan komparatif, perbandingan superlatif.